A new species of the axiid shrimp genus Manaxius Kensley, 2003 (Decapoda: Axiidea) from shallow coral reefs of the western Pacific - Komai, Tomoyuki; Anker, Arthur (Zootaxa, 2020)
Manaxius paullus, a new species of axiid burrowing shrimp, is described on the basis of a female holotype from the Society Islands, French Polynesia, and a female paratype from the Ryukyu Islands, Japan. Both specimens were collected on shallow coral reefs. The new species is morphologically closest to five of 17 congeners, viz., M. euophthalmus (de Man, 1905), M. izuensis (Komai, 2011), M. mimasensis (Sakai, 1967), M. poupini (Komai, 2016) and M. supia Poore, 2020, but can be separated from all of them by the rostrum being relatively broad and with one pair of lateral spines, in addition to a pair of supraocular spines; the presence of a subdistal spine on the dorsal margin of the cheliped ischium; the presence of additional three or four small spines on each cheliped palm, adjacent to the dorsal margin; and the lack of a spine near the base of the fingers of each cheliped palm.